Vaginoperineal Fistula as a Complication of Perianal Surgery in a Patient with Sjögren’s Syndrome: A Case Report - Kemal Beksac; Mert Turgal; Derman Basaran; Omer Aran; M. Sinan Beksac (Case Reports in Rheumatology, 2014)
Forty-seven-year-old woman with Sjögren’s syndrome had been operated on because of transsphincteric perianal fistula secondary to perianal abscess. Vaginal wall injury occurred during the course of the operation and injured tissue was repaired primarily. Three months later, patient suffered from the recurrence of perianal fistula symptoms and fistulectomy was performed once again under antibiotic suppression. Several months later, perineal discharge continued, and, therefore, patient was admitted to the hospital for the third time and a fistulotomy was performed. Two months after the third operation, patient was admitted with leukorrhea and a perineovaginal fistula was detected. This time, not only her surgical problem but also her immune system disorder was considered in the preoperative workup. Then, patient was hospitalized for the fourth time and “fistulectomy/perineoplasty” was performed successfully. We believe that patients with autoimmune disorders with or without medical treatment may have healing problems during the course of surgical processes and therefore such medical problems must be taken into consideration by the surgeons.